MAKNA SIMBOLIK TRADISI BELAMIN PADA MASYARAKAT DI DESA MULIA KERTA KABUPATEN KETAPANG - Karpina Karpina; Agus Sastrawan Noor; Ika Rahmatika Chalimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aimed to know the symbolic meaning of the tradition of belamin on the community in Mulia Kerta Village, Ketapang Regency. The method used qualitative descriptive. The data source used representative of traditional adat leaders. The techniques of data collections were observation, interviews, and documentation. The results obtain were: 1. This tradition adopted during Hindu culture precisely in the 16th century aimed at cleanse themselves and while the belamin process was taught character education and religious education, 2. The implementation of the tradition of belamin on the community of Desa Mulia Kerta is carrying out through several stages including: the stages of preparation, the stages carried out in the lamin / room, step down lamin, preparation for bathing, doing the betitik process, and the final stage (Khataman Al-Qur'an and Betimbang), 3. In this tradition of belamin there are several values contained such as: the value of divinity education, the value of social and community education, and the value of social and community education.Keywords: Symbolic Meaning, Belamin Tradition, Ketapang Community